2005
DOI: 10.1093/jhered/esi084
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis in the Expression of Relevant Traits in Cassava (Manihot esculenta Crantz) for Subhumid Conditions

Abstract: There is limited knowledge on the inheritance of agronomic traits in cassava and the importance of epistasis for most crops. A nine-parent diallel study was conducted in subhumid environments. Thirty clones were obtained from each F1 cross. Each clone was represented by six plants, which were distributed in three replications at two locations. Therefore the same 30 genotypes of each F1 cross were planted in the three replications at the two locations. Analysis of variance suggested significant genetic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…These findings confirm the conclusions of numerous diallelic studies conducted with both Latin American (Cach et al 2005(Cach et al , 2006Calle et al 2005;Jaramillo et al 2005;Pérez et al 2005a,b) and African cassava (Zacarias and Labuschagne 2010;Kulembeka et al 2012;Tumuhimbise et al 2014;Chalwe et al 2015) germplasm (see also Ceballos et al 2015). In agreement with the findings of Ly et al (2013), we found cassava mosaic disease severity (MCMDS) to be well predicted with an additive only model.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings confirm the conclusions of numerous diallelic studies conducted with both Latin American (Cach et al 2005(Cach et al , 2006Calle et al 2005;Jaramillo et al 2005;Pérez et al 2005a,b) and African cassava (Zacarias and Labuschagne 2010;Kulembeka et al 2012;Tumuhimbise et al 2014;Chalwe et al 2015) germplasm (see also Ceballos et al 2015). In agreement with the findings of Ly et al (2013), we found cassava mosaic disease severity (MCMDS) to be well predicted with an additive only model.…”
Section: Discussionsupporting
confidence: 92%
“…We then assessed the accuracy of genomic prediction of additive compared to total (additive plus nonadditive) genetic value. Using several approaches and datasets based on genome-wide marker data, we confirmed previous findings in cassava based on diallel crosses nonadditive genetic variation is significant, especially for yield traits (Cach et al 2005(Cach et al , 2006Calle et al 2005;Jaramillo et al 2005;Pérez et al 2005a,b;Zacarias and Labuschagne 2010;Kulembeka et al 2012;Tumuhimbise et al 2014;Ceballos et al 2015;Chalwe et al 2015). A potential weakness of the marker system we used (GBS) is that it generates a high proportion of missing marker data and it may undercall heterozygotes when read depth is insufficient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…using genetic engineering or conventional breeding) has to be watched closely because modifications in a particular trait might have impact on other characteristics of the roots (epistasis). Cach et al, 2005 reported that there is paucity of knowledge on the inheritance of agronomic traits in cassava and the importance of epistasis. It however appears that epistasis is very likely to occur for non-negligible number of traits in cassava.…”
Section: Minerals and Vitaminsmentioning
confidence: 99%
“…Dominance and epistasis are significant for fresh root and foliage yields . A significant epistasis may explain the difficulty of quantitative genetic models and QTL for accounting phenotypic variation of cassava traits with complex inheritance (Cach et al 2005). Prediction accuracy must improve for genomic selection to outperform phenotypic selection on a per-year basis, for example, by increasing training population size or becoming less dependent on historical datasets (Ly et al 2013).…”
Section: Cassavamentioning
confidence: 99%